تأثير المبادأة والابتكار في تحقيق الميزة التنافسية المستدامة دراسة ميدانية على المطاعم السياحية في محافظة اللاذقية - زاهر, بسام; لايقة, هشام (Latakia University Journal - Economic and Legal Sciences Series, 2018)
This study aimed to identify the reality of proactive and innovation the elements of sustainable competitive advantage (knowledge - creating obstacles to imitating the product of the organization), as well as the impact of innovation and innovation in gaining sustainable competitive advantage among the employees of tourist restaurants in Lattakia. In order to achieve the objectives of the study, the researcher developed a questionnaire to collect data. The research community included all the workers in the small and medium restaurants in Lattakia. The researcher chose a soft sample of the senior management staff which included (88) employees, the questionnaires were distributed to them, (67) questionnaire for analysis. The study concluded that the reality of the strategy of proactive and innovation is good in restaurants, and that the reality of the advantage of knowledge and the creation of impediments to imitating the organization's product is good in restaurants, and that there is a statistically significant relationship between the strategies of proactive and innovation and gaining the advantage of knowledge, which is a week relationship (69)%, There is also a statistically significant relationship between the strategies of proactive and innovation and gaining the advantage of creating impediments to imitating the product of the organization which is a strong relationship (90)%. هدفت هذه الدراسة إلى التعرف على واقع المبادأة والابتكار وعناصر الميزة التنافسية المستدامة (المعرفة- خلق عوائق تقليد منتج المنظمة)، وكذلك تأثير المبادأة والابتكار في كسب ميزة تنافسية مستدامة لدى العاملين في المطاعم السياحية في مدينة اللاذقية. ولتحقيق أهداف الدراسة فقد طوّر الباحث استبانه لجمع البيانات، شمل مجتمع البحث جميع العاملين في المطاعم الصغيرة والمتوسطة في اللاذقية، وقد اختار الباحث عينة ميسرة من موظفي الإدارة العليا شملت (88) موظف، تم توزيع الاستبيانات عليهم، وتم استرجاع (71)، وبالتالي خضع (67) استبياناً للتحليل. خلصت الدراسة إلى نتائج أهمها إنّ واقع استراتيجية المبادأة والابتكار جيد في المطاعم، وأن واقع ميزة المعرفة وخلق عوائق تقليد منتج المنظمة جيد في المطاعم, وأن هناك علاقة ذات دلالة احصائية بين استراتيجيتي المبادأة والابتكار وكسب ميزة المعرفة وهي علاقة ضعيفة إذ بلغت (69)%، وكذلك يوجد علاقة ذات دلالة احصائية بين استراتيجيتي المبادأة والابتكار وكسب ميزة خلق عوائق تقليد منتج المنظمة وهي علاقة قوية إذ بلغت (90)%.